Memanajemen Komunikasi Antara Orang Tua Dan Anak Untuk Menciptakan Keluarga Yang Harmonis - Andi Rahmat; Anton Widodo; Nur Fauziah Fatawi (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2022)
Parents have a crucial role in educating their children, especially in instilling Islamic values ​​in their children. Children are early in age, they are made & educated from the very beginning. In Islam, it is the responsibility of parents to provide education according to their nature, namely faith in Allah SWT. This fitrah is a basic operational concept based on the process of human creation. It contains the potential power to grow and develop aphorically and direct it to achieve the goal of its creation. Parents and children usually have a closer interaction. The task of parents in raising children in a family environment is very difficult. Because the family is the main location for the development of the child who receives the impact based on the part of the family, both positively and negatively. The research used in this observation is a qualitative narrative research. This study uses direct surveys and interviews. According to the output of the method, the output of the interpersonal dialogue carried out by the family hypnotizes the success of growing knowledge of trust in children because if the family often gives examples of good advice and good behavior. The baby wants to do what his parents want and grow the insight of the child's belief. in this case not only provide input or direction